2020
DOI: 10.1007/s00167-020-06076-4
|View full text |Cite
|
Sign up to set email alerts
|

Difference of preoperative varus–valgus stress radiograph is effective for the correction accuracy in the preoperative planning during open-wedge high tibial osteotomy

Abstract: Purpose This study aimed to evaluate (1) the eicacy of varus-valgus stress radiographs to adjust the preoperative softtissue imbalance and (2) ascertain whether varus-valgus stress radiographs are efective for the correction accuracy in the preoperative planning of the opening wedge high tibial osteotomy (OWHTO). Methods From February 2017 to December 2018, a total of 121 consecutive knees that underwent bi-planar OWHTO were enrolled in this retrospective analysis. Preoperative planning was performed using a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…It has been reported that joint laxity, especially on the lateral side, could affect lower-extremity alignment following HTO [ 2 , 14 ]. The surgical pearls for successful MOWHTO include representation of weight-bearing alignment of the patient, who is in the supine position during surgery [ 2 , 14 , 36 , 37 ]. In fact, there have been many studies examining the relationship between factors related to joint laxity, including JLCA, to predict the actual standing alignment of MOWHTO patients [ 2 , 14 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that joint laxity, especially on the lateral side, could affect lower-extremity alignment following HTO [ 2 , 14 ]. The surgical pearls for successful MOWHTO include representation of weight-bearing alignment of the patient, who is in the supine position during surgery [ 2 , 14 , 36 , 37 ]. In fact, there have been many studies examining the relationship between factors related to joint laxity, including JLCA, to predict the actual standing alignment of MOWHTO patients [ 2 , 14 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical pearls for successful MOWHTO include representation of weight-bearing alignment of the patient, who is in the supine position during surgery [ 2 , 14 , 36 , 37 ]. In fact, there have been many studies examining the relationship between factors related to joint laxity, including JLCA, to predict the actual standing alignment of MOWHTO patients [ 2 , 14 , 36 , 37 ]. However, there continue to be limitations to the prediction of postoperative alignment through radiation measurements related to joint laxity before surgery [ 2 , 14 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intersection of these straight lines involves mechanical [14], [15] or anatomical axes [16] It is also influenced by the need or regulation of the osteotomy itself i.e. varus gene defect [14], valgus [17] or recurvatum [18]. This selection also depends on the selection of wedges to be used that is whether open wedge, closed, dome and also a combination.…”
Section: Introductionmentioning
confidence: 99%